PERBANDINGAN PEMAKAIAN BAHAN BAKAR MINYAK ANTARA KENDARAAN RODA DUA MANUAL DAN MATIC - Ayatullah Ayatullah; Renni Anggraini; Sofyan M. Saleh (Prodi Magister Teknik Sipil Unsyiah, 2018)
Ownership of motorcycles as an alternative mode of choice is an affordable and economical increase along with the convenience offered by many dealers. However, there is no precise model to describe Vehicle operational cost (BOK) information of motorcycles based on the use of fuel oil. The purpose of this study is to identify the effect of the speed of two-wheeled vehicles to the consumption of fuel oil based on the type of motorcycle (manual or automatic), determine the appropriate model and as reference data for transportation feasibility studies especially for motorcycle. The research conducted on the main road of Banda Aceh City with five different mean speed to reach 50 km distance. The result analysis is done by using SPSS program with linear or nonlinear regression. Model of the influence of the speed of two-wheeled vehicles to the consumption of fuel oil (BBM) based on the type of motorcycle for manual Y = 0,598 + 0,003X, for automatic that is Y = 0,427 + 0,099X-0,004X2 + 0,00003750X3. The result shows that the manual saw a tendency of linear increase for the use of fuel oil for each average speed. Motorcycle automatic is an upside trend that the greater the speed, the smaller the use of oil fuel volume, especially at the speed of 40 km/hour and 50 km/hour seen a significant decrease and increased at speeds above 50 km/hour. This study can be a recommendation to choose an efficient motor vehicle from BOK based on the use of fuel oil.